Decreasing climate change vulnerability through adaptation with special reference to migration: a study in the Indian Sundarbans - Chatterjee, Subarna (Kansas State University, 2021)
The Indian Sundarbans is a hotspot of global climate change. This delta harbors 4.3 million people who are mostly dependent on natural resources for their livelihood and are vulnerable to impacts of erosion, salinization of agricultural lands, rainfall variability, and tropical cyclones. This study aims to understand how residents of the coastal areas including deltas and small islands adapt to environmental changes and problems. It specifically focuses on migration as an adaptation. It uses household level primary data collected by interviewing 300 participants from 10 different villages of the eastern and western parts of the Indian Sundarbans. Through a mixed method of data analysis this study examines people’s perception of environmental change and its impacts, adaptation practices, particularly the different ways migration is being used as an adaptation, the environmental and non-environmental determinants of adaptive migration, and people’s willingness to permanently relocate to environmentally safer places in the future. The results show that residents perceived significant environmental changes and problems in the last 10 years in the Sundarbans. To reduce the impacts of such change they mostly preferred in-situ structural and non-structural adaptation measures but 58% of the households pursued temporary migration as an adaptation strategy. Temporary migration was pursued as a reactive strategy to cope with the economic impacts of natural hazards or disasters, or as a livelihood diversification strategy for present economic security and to prepare for future hazards or as an alternative income source for the households that suffered irrevocable losses of agricultural lands due to erosion. The remittances from migration helped in household consumption and small-scale investments in non-farm economies. This study also revealed that even though remittances reduced the impacts of natural hazards, environmental change and problems were not the determining factors of migration but acted as catalysts of migration by negatively influencing agricultural income. The probability of migration was greatest among the households that relied on agriculture as the only livelihood and decreased as households shifted to non-farm livelihoods. Among the environmental factors, erosion was found to be the only statistically significant determinant of migration. While labor migration was widely used as an adaptation, 92% of the residents were not willing to permanently relocate away from their native villages in the Sundarbans despite perceiving environmental risk. These residents shared a deep sense of belonging with their birthplaces and communities. They have lived through environmental problems and believed that unpredictability in the potential destination cities is riskier than environmental changes in the Sundarbans. More importantly, they lacked the resources needed to relocate with families. However, a few households—mostly from the erosion affected places—were willing to relocate if the government provided them with free lands and jobs.
Keywords: Climate change; Migration; Adaptation; Bengal Delta